2021
DOI: 10.1016/j.invent.2021.100432
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality facial emotion recognition in social environments: An eye-tracking study

Abstract: Background Virtual reality (VR) enables the administration of realistic and dynamic stimuli within a social context for the assessment and training of emotion recognition. We tested a novel VR emotion recognition task by comparing emotion recognition across a VR, video and photo task, investigating covariates of recognition and exploring visual attention in VR. Methods Healthy individuals (n = 100) completed three emotion recognition tasks; a photo, video and VR task. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 44 publications
(73 reference statements)
3
27
1
Order By: Relevance
“…We found a main effect of age on emotion recognition accuracy, replicating other studies. 18 , 19 Contrary to previous meta-analyses on (non-VR) SCT finding associations between emotion perception and gender, hospitalization status, clinical symptoms and antipsychotic treatment, 20 we found no other predictors or moderators of accuracy. This could be due to the absence of an effect, interference due to the interrelatedness of time and task difficulty, and/or insufficient power to detect moderation effects.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We found a main effect of age on emotion recognition accuracy, replicating other studies. 18 , 19 Contrary to previous meta-analyses on (non-VR) SCT finding associations between emotion perception and gender, hospitalization status, clinical symptoms and antipsychotic treatment, 20 we found no other predictors or moderators of accuracy. This could be due to the absence of an effect, interference due to the interrelatedness of time and task difficulty, and/or insufficient power to detect moderation effects.…”
Section: Discussioncontrasting
confidence: 99%
“…The question, therefore, remains to what degree improvements in VR generalize to performance on other social cognitive tasks and daily life. As pointed out in the Introduction, a study 18 using the same VR environment found that performance and confusion patterns across the VR task, a photo task (Ekman 60 Faces Test), and a video task 34 were comparable in healthy individuals.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Traditional therapeutic tools are limited to psychotherapy and drug therapy. The development of VR technology has promoted its application in this field, including a series of studies aimed at assessing and improving symptoms of schizophrenia [ 63 ], as well as VR emotion recognition tasks aimed at treating facial emotion recognition disorders in patients with neurological and psychiatric disorders in recent years [ 64 , 65 ]. To develop VR into a mature tool for improving mental health, researchers need to integrate knowledge from health care, computer science, neuroscience, psychology, social cognition, multisensory perception, and multimedia development in an interdisciplinary approach [ 27 ] and specifically combine user needs.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of perspective taking research, task stimuli can vary between pictorial representations of people [ 68 ] to live tasks presented by a confederate [ 69 ]. Similarly, in emotion recognition research, the task stimuli can vary from static, regimented presentations of actors such as those outlined by Eckman [ 70 ] to more complex emotional stimuli presented via video presentations or, relatively recently, via virtual reality avatars [ 37 , 71 ]. Yet, despite the clear differences in social complexity in the stimuli used in these paradigms, it is not yet understood if these differences lead to empirical alterations of behaviour.…”
Section: Moving Beyond Social Attention: the Effect Of Social Presenc...mentioning
confidence: 99%